Proceedings of the International Joint Conference on Neural Networks, 2003.
DOI: 10.1109/ijcnn.2003.1223655
|View full text |Cite
|
Sign up to set email alerts
|

T-maze training of a recurrent CA3 model reveals the necessity of novelty-based modulation of LTP in hippocampal region CA3

Abstract: Abstract-The rat hippocampus has been shown to mediate a large set of spatial navigation tasks such as the simple T-maze. We investigated the performance of a minimal computational, but biologically based, model of CA3 on this task. For successful performance, the model needs to generate and maintain neuronal codes for each of the two arms of the T-maze. Moreover, each code must be distinctively recalled in a goal-dependent manner. The development of such neuronal codes is aided by the appearance of repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Early theoretical models suggested that hippocampal sequences, learned via phase precession and/or temporally asymmetric synaptic plasticity, enabled context-dependent predictions of future positions [6468]. Experimental studies revealed theta-rhythmic forward-sweeping sequences during active locomotion [69, 70] that mentally probed paths ahead of the animal’s current position to guide navigational decisions [71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…Early theoretical models suggested that hippocampal sequences, learned via phase precession and/or temporally asymmetric synaptic plasticity, enabled context-dependent predictions of future positions [6468]. Experimental studies revealed theta-rhythmic forward-sweeping sequences during active locomotion [69, 70] that mentally probed paths ahead of the animal’s current position to guide navigational decisions [71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even if asymptotic stability does not obtain, the large number of training trials required to produce a collapse might be enough to ignore in practical situations; i.e., across training trials, there are many trials of correct prediction, and this run of successes would be biologically useful. Elsewhere we have discussed such an idea, that transient, successful prediction is useful if the hippocampus can be taken off-line (see Monaco and Levy (2003) for other observations and biological interpretations concerning unstable but transiently useful hippocampal encodings).…”
Section: Code Stabilizationmentioning
confidence: 99%
“…Studies show that when rats deliberate in a T-maze, neurons in their hippocampus fire as though they were exploring the two options in the maze (Johnson et al, 2007; Johnson & Redish, 2007). A simulation study of T-maze decision making using the present hippocampal model has demonstrated activity in both paths in the model (Monaco & Levy, 2003). Although it is clear that this delayed activation could be used to select actions based on eventual outcomes, it is not immediately obvious whether or how this mechanism might lead to discounting of those delayed rewards.…”
Section: Resultsmentioning
confidence: 85%